(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
One of the most important food crops for Indonesian people is rice. The research location is Klaru Village in Mariat District, Sorong Regency. The experiment will take place from March to May, 2024. This study was carried out using experimental methods through field trials. Randomized Block Design, or randomized group design, consists of four stages of super bokashi MA-11 organic fertilizer treatment, namely A0 = no fertilizer (control), A1 = 5 tonnes/ha (3.125 kg/plot), A2 = 7 tonnes/ha (4,375 kg/plot), and A3 = 9 tons/ha (5,625 kg/plot). The research results showed that the application of superbokashi MA-11 organic fertilizer increased the growth and production of Mekongga rice varieties. Average production ranged between 4.08 tonnes/ha and 6.94 tonnes/ha. The highest production of 6.94 tons/ha was achieved with a dose of 9 tons/ha, followed by 6.10 tons/ha with a dose of 7 tons/ha, and 5.50 tons/ha with a dose of 5 tons/ha. In the treatment without fertilizer, the lowest yield reached 4.08 tons/ha. LoA, Kor